Health Status and Prognosis of Disease Prevalence Among Adolescents in Ukraine - T.V. Peresypkina (Zaslavsky O.Yu., 2014)
The article provides an analysis of the health status of adolescents in Ukraine; the tendencies and dynamics of changes in the structure of disease prevalence among adolescents are determined using the method of prognosis.